How social context impacts on the development, identification and treatment of mental and substance use disorders among young people – a qualitative study of health care workers. (13th January 2015) - Leahy, D.; Schaffalitzky, E.; Armstrong, C.; Latham, L.; McNicholas, F.; Meagher, D.; Nathan, Y.; O'Connor, R.; O'Keane, V.; Ryan, P.; Smyth, B. P.; Swan, D.; et al.
Abstract : Introduction: Social context has a major influence on the detection and treatment of youth mental and substance use disorders in socioeconomically disadvantaged urban areas, particularly where gang culture, community violence, normalisation of drug use and repetitive maladaptive family structures prevail. This paper aims to examine how social context influences the development, identification and treatment of youth mental and substance use disorders in socioeconomically disadvantaged urban areas from the perspectives of health care workers. Method: Semi-structured interviews were conducted with health care workers ( n =37) from clinical settings including: primary care, secondary care and community agencies and analysed thematically using Bronfenbrenner's Ecological Theory to guide analysis. Results: Health care workers' engagement with young people was influenced by the multilevel ecological systems within the individual's social context which included: the young person's immediate environment/'microsystem' (e.g., family relationships), personal relationships in the 'mesosystem' (e.g., peer and school relationships), external factors in the young person's local area context/'exosystem' (e.g., drug culture and criminality) and wider societal aspects in the 'macrosystem' (e.g., mental health policy, health care inequalities and stigma). Conclusions: In socioeconomically disadvantaged urban areas, social context, specifically the micro-, meso-, exo-, and macro-system impact both on the young person's experience of mental health or substance use problems and services, which endeavour to address these problems. Interventions that effectively identify and treat these problems should reflect the additional challenges posed by such settings.